Health information system as an integral component of cardiovascular surveillance system in Nepal - Dhungana, Sahadeb Prasad; Karmacharya, Robin Man; Pyakurel, Prajjwal; Shrestha, Archana; Vaidya, Abhinav (Nepalese Heart Journal, 2019)
Introduction: Nepal lacks a comprehensive, integrated health information system (HIS) to address the growing burden of cardiovascular diseases (CVDs). Method: We performed a literature search and reviewed papers, government reports, and websites related to HIS. We included existing situations of HIS, major gaps, strength weakness opportunity threat (SWOT) analysis and role of different stakeholders to address CVD burden in Nepal. Results: Health data from different health facility level are filled in district health information software (DHIS-2). DHIS-2 has been implemented in 10 districts in full-fledged manner and partial phase in 22 districts. Data are collected by means of paper-based registers, tally sheets, and monthly data collation forms. The collated data are sent monthly to the district level and entered into the computer using DHIS-2 software and submitted to the national health departments. Major gaps in health management information system (HMIS) are lack of separate heading of CVDs and lack of implementation of the existing data collection system. The strengths of the HIS are robust and decentralized health care delivery system in a good number of medical institutions. Weakness is lack of public and private partnership, concrete policy on health information and dissemination. Opportunities are the existence of policies and regulations mandating health facilities to report indicators, the involvement of private institutions and the expansion of existing DHIS-2 system. Conclusion: Nepal currently lacks reliable and accurate data on timely manner to address the growing burden of CVDs. There is a need to strengthen the existing DHIS with a commitment from expertise and leadership.